2012
DOI: 10.1159/000335783
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin May Delay Cardiac Aging by Upregulating Peroxisome Proliferator-Activated Receptors in Rats

Abstract: Aims: To investigate the effect of atorvastatin on cardiac aging in rats. Materials: Ninety 20-month-old Wistar rats were administered oral atorvastatin (AVT; 10 or 1 mg·kg-1·day-1) or saline for 4 months. At the end of the experiment, age-related changes in hearts were measured. Results: Compared with young rats, obvious increases were found in the aging rats in left ventricle thickness, diameter of cardiocytes, collagen deposition, the ratio of type I/type III collagen, β-galactosidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…This plateau effect has also been confirmed by many other investigators when compared between different doses of statins (16). Besides the mechanism mentioned above, statins may upregulate PCSK9 concentrations by peroxisome proliferator-activated receptor (PPAR) related pathway (21,22) or sterol regulatory element binding protein-2 (SREBP-2) associated mechanism (7,(23)(24)(25). However, ezetimibe has not been discovered with such pleiotropic effects.…”
Section: Discussionmentioning
confidence: 63%
“…This plateau effect has also been confirmed by many other investigators when compared between different doses of statins (16). Besides the mechanism mentioned above, statins may upregulate PCSK9 concentrations by peroxisome proliferator-activated receptor (PPAR) related pathway (21,22) or sterol regulatory element binding protein-2 (SREBP-2) associated mechanism (7,(23)(24)(25). However, ezetimibe has not been discovered with such pleiotropic effects.…”
Section: Discussionmentioning
confidence: 63%
“…In the present study although the gene expression of some inflammatory markers such as COX-2, IL-6, or IL-1β was not modified in response to aging, we found an overexpression of iNOS and TNF-α in the heart of 24-month-old rats. Likewise the expression of these factors have been found to be increased both in the heart (Han et al, 2012) and in coronary arteries (Csiszar et al, 2002(Csiszar et al, , 2003 restriction for three months did not prevent aging-induced increase of iNOS and TNF-α. The same protocol of caloric restriction did not prevent aging-induced changes in the expression of TNF-α in other tissues such as the liver or the adipose tissue (Horrillo et al, 2011), which could be explained by either the small reduction in caloric intake (20%) or by the short duration of caloric restriction (3 months).…”
Section: Months 24 Months 24 Months + Caloric Restrictionmentioning
confidence: 95%
“…Metabolomic analysis indicated an age-dependent decrease in cardiac glucose content, signs of decreased ketone supply, and altered FA synthesis (62). The importance of PPARα inhibition in accelerating cardiac aging was demonstrated in 20-month-old rats that were treated with the lipid lowering drug atorvastatin, which increases PPARα expression (63). The treatment with atorvastatin reduced cardiac hypertrophy, collagen deposition, oxidative stress, expression of inflammatory cytokines, and the aging marker β-galactosidase.…”
Section: Role Of Pparα In Aging-related Cardiomyopathymentioning
confidence: 99%
“…The treatment with atorvastatin reduced cardiac hypertrophy, collagen deposition, oxidative stress, expression of inflammatory cytokines, and the aging marker β-galactosidase. The conclusion about the association of PPARα inhibition and cardiac aging was further emphasized when pretreatment with PPAR inhibitors attenuated the effect of atorvastatin on the inhibition of inflammatory cytokines (63). This indicated that the beneficial effects of atorvastatin on cardiac aging may be attributed to either lipid lowering effect or the anti-inflammatory role of PPAR signaling (64,65).…”
Section: Role Of Pparα In Aging-related Cardiomyopathymentioning
confidence: 99%